GLP-1 and glucagon receptor dual agonism ameliorates kidney allograft fibrosis by improving lipid metabolism - Peng, Linjie; Lai, Weijie; Yu, Shuangjin; Li, Qihao; Jiang, Xianxin; Chen, Guodong (Frontiers in Immunology, 2025)
IntroductionKidney allograft fibrosis accelerates the progression of chronic kidney disease (CKD), leads to allograft failure, and increases patient mortality. Emerging evidence suggests that metabolic syndrome in transplant recipients is associated with fibrosis development. However, it remains unclear whether targeting metabolic pathways can mitigate allograft fibrosis. This study aimed to explore the potential of targeting metabolic pathways using the GLP-1R/GCGR dual agonist TB001 for the treatment of kidney allograft fibrosis.MethodsKidney allograft fibrosis was induced in rat kidney transplant models. Histological analysis, transcriptome sequencing, and in vitro experiments were performed to investigate the efficacy of TB001 and its underlying mechanisms.ResultsCompared with the control group, TB001-treated recipients had significantly improved kidney allograft function, as evidenced by lower creatinine and 24-hour urine protein levels. Moreover, TB001 treatment decreased the body weight and serum total cholesterol, LDL-cholesterol, and TNF-α levels in transplant recipients, indicating metabolic improvements. Pathological analysis demonstrated that TB001 treatment reduced inflammatory cell infiltration and downregulated the expression of fibrosis markers, including TGF-β1, α-SMA, COL1A1, and Vimentin. Further transcriptome sequencing of kidney grafts revealed that TB001-treated group had a gene expression pattern similar to that of the syngeneic control group and showed significant enhancement of lipid metabolism-related pathways, particularly the PPAR pathway. In vivo and in vitro experiments further demonstrated that TB001 upregulated the expression of CPT1A, a key molecule involved in lipid metabolism, and inhibited TGF-β1/Smad2/3/Twist and PKC-α/PKC-β pathways.ConclusionTargeting metabolic pathways using the GLP-1R/GCGR dual agonist TB001 shows potential for managing kidney allograft fibrosis.